An Electrochemically-Active Biosensor to Study the Development of Biofilm in Wild-Type and Fimbriae- Deficient E. coli Mutants - Yavarinasab, Adel; He, Jerry; Tropini, Carolina (CMBES Proceedings, 2023)
Biofilms are clusters of bacterial aggregates, encased in a self-produced matrix of extracellular polymeric substances and adherent to the surface. Biofilms pose significant consequences in medical settings, associated with 80% of microbial and 60% of all infections, originating in a hospital. A standard technique for biofilm determination is through crystal violet staining. An irreversible as-say, it produces inconsistent responses in the case of different mutants or antimicrobial agents. To address this, a novel biosensor has been developed to investigate E. coli biofilm life cycle by selecting wild-type (WT) and strains without fimbriae (genes involved in biofilm formation – fimC and fimD) mutants.